2007
DOI: 10.1111/j.1460-2695.2006.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Specimen aligning techniques in tensile and fatigue tests for thin films

Abstract: A B S T R A C T Measurements of the mechanical properties of a thin film are strongly influenced by the test procedures. The aim of this paper is to introduce specimen aligning techniques for tensile and fatigue tests with thin films. The calculated modulus for polycrystalline silicon can vary from 100 to 160 GPa according to the alignment condition and reaches a peak at the best alignment as determined from an extensive pre-tensile test. The 'modulus alignment method' is utilized to ensure the specimen alignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Alternatives are electro-static clamping [53] and mechanical locking via pin-in-hole [54] or geometries that conform to the gauge-end [55]. However, in all cases careful provisions for specimen alignment are necessary [56][57][58][59][60][61][62]. Transverse and rotational misalignment may occur between the specimen's longitudinal axis and the setup's loading axis.…”
Section: Design Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatives are electro-static clamping [53] and mechanical locking via pin-in-hole [54] or geometries that conform to the gauge-end [55]. However, in all cases careful provisions for specimen alignment are necessary [56][57][58][59][60][61][62]. Transverse and rotational misalignment may occur between the specimen's longitudinal axis and the setup's loading axis.…”
Section: Design Principlementioning
confidence: 99%
“…In [62] image processing has been employed to measure the rotational misalignment. Adequate alignment can also be established through repeated elastic loading and alignment adjustment until a maximum of the measured modulus is obtained [59]. Alternatives to ameliorate misalignment effects are: the elimination of unwanted kinematic degrees of freedom of the specimen, e.g.…”
Section: Design Principlementioning
confidence: 99%
“…Sample misalignment will yield artificially low mechanical properties due to bending, as documented by Kim and co-workers. [33] This error is lessened, although not eliminated via careful seating and alignment of the specimen within the grips to ensure that the specimen is centered and contacts both edges of the grip simultaneously. The viewing perspective in the microscope provides high resolution observation of misalignment in this plane.…”
Section: Sources Of Errormentioning
confidence: 99%
“…There are numerous reports in the literature regarding microscale fatigue testing. However, these efforts are typically targeted at characterizing the mechanical response of small scale structures such as thin films, [33] micro-wires, [29,34] solder interconnects, [35] or micro-electro-mechanical systems (MEMS). [36][37][38] Since small scale devices are intended for use in specific applications, much of the research on these devices often focuses on identifying the environmentally driven…”
mentioning
confidence: 99%
“…However, the standard has been applied to the tensile test of bulk material and can be applied to the tensile test of thin film because the strain sensors or components of the strain sensors must be attached to the specimen. Oh et al have suggested the 'modulus alignment method' based on the fact that the better the alignment, the higher the modulus to ensure the specimen alignment before tensile and fatigue tests [18]. In this method, an extensive pretensile test which may affect the test results must be performed before the tensile or fatigue test.…”
Section: Introductionmentioning
confidence: 99%